Accurate estimation of tube-induced distortion effects on wind pressure measurements. Issue 188 (May 2019) - He, Y.C.; Liang, Q.S.; Li, Z.; Fu, J.Y.; Wu, J.R.; Deng, T.
Abstract: Pressure signals are commonly measured by tube-transducer systems which may result in significant distortion effects on the measurements. Although many studies have been conducted on the correction of distorted pressure records, there is a lack of investigations on determining the inner diameter (D) of pressure tubes and the inner volume (V) of pressure transducers involved in a tube-transducer system, which are demonstrated to be two key parameters for quantifying the distortion effects and for correcting the recorded pressure signals. This study presents a systematic method for accurate determination of these two parameters. The value of D is estimated first by measuring the weight of water filled in a tube. The value of V is then determined by fitting the measured frequency-response-function (FRF) with those predicted by the theoretical model. To demonstrate the validity of the proposed method, two groups of case studies are presented which utilize scanivalve and Honeywell transducers to measure wind pressure, respectively. Results show that the nominal inner diameter of some tubes may not be accurate, and the inner volume of a Heneywell transducer cannot be neglected. This study also compares raw pressure records with those after correction, through which the importance of accurate determination of D and V is highlighted. The proposed method has some attractive merits including high accuracy and great operational convenience, and it can be adopted widely in wind tunnel tests.